الحق في النفاذ إلى المعلومة - رضوان زغادنية (My University, 2025)
Summary: The right to access information is a fundamental human right, and it is an essential foundation for any state that wishes to demonstrate the transparency of its various transactions, this right is one of the pillars of good governance, And a requirement for democracy and administrative reform, According to the constitutional amendment of 2016, The Algerian constitutional founder took care of the right to access information, However, the law required for it is still absent today, despite the precedence of other regulatory legal texts, the right of citizens to access information was established, in particular decree N°: 88-131 regulating the administration's relationship with the citizen, These texts, in the majority of them, still lack the procedural mechanisms to give effect to the citizen's right to access information' this requires the haste of the legislator to issue the text that is required for this right. The Study of the provisions of the Algerian legislative system, in particular Ordinance n°: 21-09, has brought to light a trend contrary to expectations in terms of guaranteeing the principle of the right of access information, due to the inclusion of several obstacles that prevent its exercise, despite the fact that it is adorned with many principle is one of the mechanisms for its realization, especially after its elevation ti the rank of constitutional principle in 2016. ........................... الملخّص: يعتبر الحق في النفاذ إلى المعلومة أحد حقوق الإنسان الأساسية، كما يمثّل ركيزة أساسية لأية دولة ترغب في إثبات شفافية معاملاتها المتعدّدة، حيث أن هذا الحق يمثل أحد دعائم الحكم الراشد ومتطلبا من متطلبات الديمقراطية والإصلاح الإداري، حيث اهتمّ المؤسس الدستوري الجزائري بهذا الحق وقام بكفالة هذا الحق ودسترته بموجب التعديل الدستوري لسنة 2016، غير أن القانون المؤطر له مازال غائبا ليومنا هذا، بالرغم من أسبقية نصوص قانونية تنظيمية أخرى أسّست لحق المواطن في النفاذ إلى المعلومة، لاسيما المرسوم الرئاسي رقم 88-131 ، المنظم لعلاقة الإدارة بالمواطن، وتبقى هذه النصوص تفتقد في غالبيتها إلى الآليات الإجرائية الكفيلة بتفعيل حق المواطن في الحصول على المعلومة، الأمر الذي يستدعي تعجيل المشرع بإصدار النص المؤطّر لهذا الحق. كذلك من خلال استقراء أحكام من التشريعات الجزائرية، خاصة الأمر رقم 21-09، هذا الأخير أسفر عن توجّه معاكس لكل التوقعات في مجال ضمان مبدأ حق النفاذ إلى المعلومة، بسبب احتواء هذه الأحكام على عدّة عراقيل تمنع ممارسته، رغم تزيّنها بالعديد من المبادئ والتي يعدّ فيها هذا المبدأ من آليات تحقّقها، خاصة بعد ارتقائه إلى مبدأ دستوري سنة 2016. ...................... Résumé : Le droit d’accès à l’information est un droit humain fondamental et un fondement essentiel pour tout État souhaitant démontrer la transparence de ses différentes transactions. Ce droit est l’un des piliers de la bonne gouvernance et une condition nécessaire à la démocratie et à la réforme administrative. Conformément à l’amendement constitutionnel de 2016, le fondateur constitutionnel algérien a pris soin du droit d’accès à l’information. Cependant, la loi requise pour cela est toujours absente aujourd’hui. Malgré la prééminence d’autres textes juridiques réglementaires, le droit des citoyens à accéder à l’information a été établi, notamment le décret n° 88-131 régissant les relations de l’administration avec le citoyen. Ces textes, dans la plupart d’entre eux, manquent encore de mécanismes procéduraux pour donner effet au droit du citoyen à l’information. Cela nécessite la hâte du législateur à promulguer le texte nécessaire à ce droit. L'étude des dispositions du système législatif algérien, notamment l'ordonnance n° 21-09, a révélé une tendance contraire aux attentes en matière de garantie du principe du droit d'accès à l'information, en raison de l'inclusion de plusieurs obstacles qui entravent son exercice, malgré le fait qu'il soit doté de nombreux principes et constitue l'un des mécanismes de sa réalisation, notamment après son élévation au rang de principe constitutionnel en 2016.
Keywords: Keywords: Right to access to information; citizen; transparency and integrity; constitutional amendment.; الكلمات المفتاحية: الحق في النفاذ إلى المعلومة، المواطن، الشفافية والنزاهة، التعديل الدستوري.; Mots-clés : Droit d'accès à l'information; citoyen; transparence et intégrité; révision constitutionnelle.